Hubungan Antara Psychological Well Being Dengan Work Life Balance Pada Dewasa Awal Yang Bekerja Di Kecamatan Babelan - Tazkiya Nazla; Yomima Viena Yuliana (General Multidisciplinary Research Journal, 2024)
Introduction: This research describes the relationship between Psychological well-being and work-life balance in early adults who work in Babelan District Methods: This research uses quantitative methods, which use studies of correlation tests. The population that the researchers used for the research was the early adults who work in babelan district. Sampling using is convenience sampling technique. This study has 100 respondents that will be used by researchers. The measuring instruments used in this study are the Psychological well-being scale and the modified Work life balance scale. Results: According to Pearson correlation analysis, the correlation coefficient value is 0.782, this value refers to the positive influence between Psychological well-being and Work-life balance.  The positive value indicates that the higher the value of Psychological well-being, the higher the Work-life balance, and vice versa, the lower the Work-life balance, the lower the Psychological well-being. The correlation test results have a value of 0.782 or can be interpreted as 78.2%, this value explains that Psychological well-being as an independent variable has a relationship with Work-life balance as the dependent variable of 78.2%, and the remaining 21.8% is influenced by other factors not explained in the study. Conclusion and suggestion: Stating the alternative hypothesis is accepted. The higher the level of Psychological well-being, the higher the Work-life balance, and the lower the level of Work-life balance, the lower the Psychological well-being.